The Impact of Learning Outcomes of Aqidah and Ahlak on Students' Emotional Intelligence At Madrasah Aliyah - Harmathilda; M. Fikri Safwan; Abdul Khoir; Putri Munanjah; Sujai, Ahmad (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to determine the learning outcomes of the subject of aqidah akhlak on students' emotional intelligence. The learning outcomes of aqidah akhlak are interpreted as students' academic achievements in the subject of aqidah akhlak including mastery of concepts, principles, and application of moral values ​​in everyday life. While emotional intelligence refers to students' ability not only to understand other people's emotions but also to recognize, manage, and control their own emotions. This study uses a qualitative research type with data collection techniques through interviews, observations and literature studies. The sources include teachers of the subject of aqidah akhlak and students of class XI MA Islamiyah. The interviews used structured interviews with a series of questions that had been prepared and observations were carried out through direct observation of teachers and students. The results of the study showed that learning aqidah akhlak has an influence on the development of students' emotional intelligence. The implementation of Islamic teaching values ​​in everyday life, such as patience, humility, and empathy, contributes to improving students' ability to recognize and manage their own emotions and empathize with others.